2021
DOI: 10.1111/lang.12444
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Does the Involvement Load Hypothesis Predict Incidental L2 Vocabulary Learning? A Meta‐Analysis

Abstract: The involvement load hypothesis (ILH) was designed to predict the effectiveness of instructional tasks for incidental L2 vocabulary learning. In this meta-analysis we examined 398 effect sizes from 42 empirical studies (N = 4,628) to explore (a) the overall predictive ability of the ILH, (b) the relative effects of different components of the ILH (need, search, and evaluation), and (c) the influence of potential factors moderating learning (e.g., time on task, frequency of encounters or use, and test format). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 88 publications
6
61
1
Order By: Relevance
“…Our meta‐analysis was based on the recommendations of Plonsky and Oswald (2015) and was guided by other published meta‐analyses, such as those by de Vos, Schriefers, Nivard, and Lemhöfer (2018), Jeon and Yamashita (2014), Ke, Miller, Zhang, and Koda (2021), Plonsky (2011), Uchihara, Webb, and Yanagisawa (2019), and Yanagisawa and Webb (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Our meta‐analysis was based on the recommendations of Plonsky and Oswald (2015) and was guided by other published meta‐analyses, such as those by de Vos, Schriefers, Nivard, and Lemhöfer (2018), Jeon and Yamashita (2014), Ke, Miller, Zhang, and Koda (2021), Plonsky (2011), Uchihara, Webb, and Yanagisawa (2019), and Yanagisawa and Webb (2021).…”
Section: Methodsmentioning
confidence: 99%
“…NOTES 1 In this article, activity and task were used interchangeably to refer to instructional language activities that promote students' L2 vocabulary learning. 2 The included studies in the analyses were the same as Yanagisawa and Webb (2021), and the dataset was greatly overlapped with that of Yanagisawa and Webb (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Kim (2008) argued that strong evaluation might contribute to learning to the greatest extent, while Tang and Treffers-Daller (2016) found that search might contribute less than need and evaluation. Yanagisawa and Webb's (2021) meta-analysis of the ILH captured this trend revealing that evaluation had the most substantial influence, followed by need, while search was not found to have influence on learning. It is also important to note that the ILH assumes that strong need and strong evaluation have a larger impact on learning than moderate need and moderate evaluation (2 points are awarded for both strong need and strong evaluation, while 1 point is awarded for moderate need and moderate evaluation).…”
Section: Potential Approaches To Enhancing the Prediction Of Incidental Vocabulary Learningmentioning
confidence: 97%
“…is argument receives support from "Involvement Load Hypothesis." [59] It is argued that the retention of key structures to write well was, generally, conditional upon the degree of involvement in processing these structures. e peer feedback provided on the social networking might have helped the students to engage more in the learning processes of the writing aspects by increasing the involvement load.…”
Section: Discussionmentioning
confidence: 99%